Coronavirus Disease 2019 (COVID-19) in adolescents: An update on current clinical and diagnostic characteristics - De Sanctis, Vincenzo; Ruggiero, Leopoldo; Soliman, Ashraf T; Daar, Shahina; Di Maio, Salvatore; Kattamis, Christos (Acta Biomedica Atenei Parmensis, 2020)
The current outbreak of infections with SARS-CoV-2 is defined as Coronavirus Disease 2019 (COVID-19). The clinical symptoms of COVID-19 include fever, fatigue, cough, breathing difficulty that may lead to respiratory distress; a small population of patients may have diarrhea, nausea or vomiting. The highest infection rate occurs in adults; however, neonates, children, and adolescents can also be infected. As the outbreak continues to spread worldwide, attention has switched toward determinants of clinical manifes- tations and disease severity. The situation surrounding the outbreak is rapidly evolving and the information and recommendations are changing as new information becomes available. This paper summarises the cur- rent findings (April 3,2020) from a systematic literature review on the current knowledge of COVID-19 in adolescents (10-19 years according to the WHO definition) and reports the preliminary epidemiological data stated by the Italian National Institute of Health.